Disentangling the relationship between prior knowledge and entrepreneurial orientation: a bibliometric study - Espinoza-Torres, Diana (2022)
This paper analyzes the theoretical relationship between knowledge and entrepreneurship through a bibliometric study. Several indicators are drawn from the Web of Science database using the HistCite software for bibliometrics, including annual publications, citation density, and journals with the highest number of publications. For the empirical application, a qualitative approach was adopted through a case study of four companies located in Valencia with the application of a semi-structured interview. The Atlas.ti software was used to analyze the data. The results indicate a relationship between knowledge and entrepreneurship constructs through theoretical modeling, highlighting the importance of the origin of knowledge for new venture creation, knowledge commercialization processes through entrepreneurship opportunities, and the origin and transmission of knowledge in organizations with entrepreneurial orientation (EO). The main limitation is the dispersion of research topics and the exclusion of publications that did not address the investigated relationship directly. The theoretical model proposed in this study can be extended to different spheres to identify and generate entrepreneurship opportunities, especially in universities and incumbent firms. Future studies should further validate the model empirically